TOWARDS INTERNATIONALIZATION OF ENGINEERING EDUCATION - Peter N. Osipov; Vasily G. Ivanov; Yuliya N. Ziyatdinova (Высшее образование в России)
The paper describes the experience of Kazan National Research Technological University in internationalization of engineering education. Realization of the conception ofinternationalization implies carrying out the policy for development of international activities, creation of effective infrastructure for ensuring academic mobility, and formation ofmulticultural and multilanguage environment for raising the foreign language competency of the faculty. The experience shows that nowadays internationalization has become the principle of education modernization, which determines the university development areas.